LARGE SEBACEOUS CYST AT THE BUTTOCK - PEKANAN, Patchrin; RANGSITPOL, Thitiporn; TUNTIWIWAT, Chitchanok (The ASEAN Journal of Radiology, 2023)
Sebaceous cyst or epidermal cyst, epidermal inclusion cyst and epidermoid cyst is an epithelial cyst of the skin due to proliferation of surface epidermal cells within the corium, arising from occluded pilosebaceous follicles and containing a laminated, cheesy, oderiferous keratious epithelium (1). We present a case of large buttock sebaceous cyst with imaging of plain film and ultrasonography.